A BIBLIOMETRIC ANALYSIS OF VIDEO-BASED FEEDBACK IN HIGHER EDUCATION (2003-2022): TRENDS, GAPS AND FUTURE DIRECTIONS - Nagaletchimee Annamalai; Arathai Din Eak (Malaysian Journal of Learning and Instruction)
Purpose – Video-based feedback presents a unique approach characterised by a conversational narrative and instructor screen captures, enriching students' learning experiences and fostering stronger instructor-student connections. While this innovative methodology has the potential to revolutionise feedback practices in higher education, its full benefits and practical implications for improving learning outcomes remain unexplored.